Current Management of Severe Refractory Asthma in Italy: Analysis of Real-World Data. Issue 1 (2017) - Pedrini, Antonella; Rossi, Elisa; Calabria, Silvia; Dondi, Letizia; Martini, Nello
Introduction: Severe refractory asthma (SRA) occurs in asthma patients failing to achieve disease control despite high-intensity therapy, good adherence, and proper inhalation technique. Lack of disease control in asthma is associated with increased health care costs. Omalizumab, an anti-IgE monoclonal antibody, improves disease control in SRA patients by reducing the number of exacerbations. However, real-world evidence studies are needed to quantify the burden of SRA on health care systems. The aim of this study was to assess the current management of SRA in Italy by analyzing the prevalence of the disease and the economic impact of SRA patients. Methods: This observational study retrospectively analyzed data concerning adult patients registered in an Italian health care system database with either a prescription of omalizumab or at least a prescription of high-dose systemic corticosteroids from 2013 to 2014. Results: The overall prevalence of SRA was 0.04%. SRA-related costs were equally distributed among 3 cost drivers (drug treatments, hospital admissions, and outpatient services), amounting to €2, 815 per patient per year. In the subgroup of SRA patients treated with omalizumab (n = 55), costs related to hospital admissions and outpatient services decreased, while costs related to drug treatment increased. Conclusions: The study gives an important contribution to understand SRA management in Italy, by reporting the prevalence and the health care costs of SRA from administrative databases. This real-world evidence could be useful to estimate the impact of the new upcoming biological entities (e.g., omalizumab) in the changing profile of health care cost drivers in SRA management.